Abiotic rather than biotic filtering shapes the arbuscular mycorrhizal fungal communities of European seminatural grasslands. Issue 4 (15th December 2017) - Van Geel, Maarten; Jacquemyn, Hans; Plue, Jan; Saar, Liina; Kasari, Liis; Peeters, Gerrit; van Acker, Kasper; Honnay, Olivier; Ceulemans, Tobias
Summary: Although it is well known that arbuscular mycorrhizal fungi (AMF) play a key role in the functioning of natural ecosystems, the underlying drivers determining the composition of AMF communities remain unclear. In this study, we established 138 sampling plots at 46 grassland sites, consisting of 26 acidic grasslands and 20 calcareous grasslands spread across eight European countries, to assess the relative importance of abiotic and biotic filtering in driving AMF community composition and structure in both the grassland soils and in the roots of 13 grassland plant species. Soil AMF communities differed significantly between acidic and calcareous grasslands. In root AMF communities, most variance was attributable to soil variables while very little variation was explained by host plant identity. Root AMF communities in host plant species occurring in only one grassland type closely resembled the soil AMF communities of that grassland type and the root AMF communities of other host plant species occurring in the same grassland type. The observed AMF–host plants networks were not modular but nested. Our results indicate that abiotic conditions, rather than biotic filtering through host plant specificity, are the most important drivers in shaping AMF communities in European seminatural grasslands. Abstract : See also the Commentary on this article byHempel, 220 : 952–953 .